Modified high-strength polypropylene composite fiber and preparation method thereof
Modified nano calcium carbonate and basalt fibers and melt blended with polypropylene and other materials to prepare modified high-strength polypropylene composite fibers, which solved the problem of insufficient mechanical properties of polypropylene fibers and achieved high strength and Excellent mechanical properties.
Patent Information
- Application Number
- CN202411788414.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polypropylene fibers have shortcomings in mechanical properties, especially in areas with high strength requirements, which are difficult to meet application requirements.
By modifying nano calcium carbonate with 1,8-diisocyanate, it forms isocyanated calcium carbonate and is olefinized with basalt fibers, combining polypropylene, maleic anhydride and styrene-isoprene-styrene The block copolymer is melt blended to prepare modified high-strength polypropylene composite fibers.
The mechanical properties of polypropylene composite fibers are significantly improved, including strength and rigidity, strengthen the toughness and heat resistance of the fibers, and improve the dispersion and processing properties of the matrix.
Smart Images

Figure BDA0005174692800000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polypropylene fibers, in particular to a modified high-strength polypropylene composite fiber and a preparation method thereof. Background Art
[0002] Polypropylene is a widely used thermoplastic with the characteristics of low density, good chemical resistance and excellent comprehensive performance. However, polypropylene has poor impact resistance, poor toughness and poor dimensional stability, which limits the application of polypropylene plastics. Polypropylene fiber is a synthetic fiber made of polypropylene as the main raw material. It is a fiber with good comprehensive performance and wide application, with excellent properties such as light weight and good toughness. Polypropylene fiber is widely used in the fields of automotive parts, building structures, electronic and electrical components, etc. With the advancement of science and technology and market demand, people have put forward higher requirements on the performance of polypropylene fibers, especially in some fields that require high strength, it is necessary to modify polypropylene fibers to broaden their application fields.
[0003] Using inorganic nanomaterials as fillers to enhance and modify polypropylene fibers can play an enhancing role. Chinese patent application CN110818998A discloses a method for preparing a polypropylene / carbon nanotube fiber composite material, wherein PP, silane coupling agent-modified carbon nanotubes and a series of additives are melt-blended in a twin-screw extruder and melt-spinned to obtain carbon nanotube-modified polypropylene fibers, and these fibers are interlaced and arranged to form a mesh structure. The composite material has the characteristics of high strength, but the dispersion of carbon nanotubes in the polypropylene matrix is general, which affects the overall performance. Chinese patent application CN102383214A discloses a polypropylene crude fiber and a preparation method thereof. The polypropylene crude fiber comprises a mixture of 85-99% polypropylene, 0.1-10% inorganic filler, 0.5-5% bulking agent, 0.1-0.5% antioxidant, and 0.1-0.3% ultraviolet absorber, which is extruded by a twin-screw extruder and spun by a spinneret, and then subjected to water cooling, hot water drawing, hot roller drawing, and heat setting to form a crude fiber, and finally the crude fiber is subjected to surface indentation treatment. The invention has a simple production process and low cost. Polypropylene is modified with a low-cost inorganic filler to obtain a high-strength and high-modulus polypropylene crude fiber, but the dispersibility and compatibility of the inorganic filler in the matrix are poor. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides a modified high-strength polypropylene composite fiber and a preparation method thereof, which solves the problem of mechanical properties of polypropylene fibers.
[0006] (II) Technical solution
[0007] In order to achieve the above object, the present invention discloses a method for preparing a modified high-strength polypropylene composite fiber, comprising the following steps:
[0008] Step 1: Ultrasonically disperse nano calcium carbonate in N,N-dimethylformamide, mix well, add 1,8-diisocyanate, heat and stir to react, filter after the reaction is completed, wash with anhydrous ethanol, and dry in a drying oven at 80°C for 12 hours to obtain isocyanate calcium carbonate;
[0009] Step 2: ultrasonically disperse isocyanate calcium carbonate in N,N-dimethylformamide, mix well, add 1,3-bis(aminopropyl)tetramethyldisiloxane and stannous octoate, heat and stir to react, and after the reaction is completed, perform vacuum distillation, wash with anhydrous ethanol, and dry in a drying oven at 80° C. for 12 hours to obtain amino calcium carbonate;
[0010] Step 3: Use acetone to ultrasonically clean the basalt fiber for 4 hours, transfer it to an ethanol solution after cleaning, add γ-methacryloxypropyltrimethoxysilane, stir and mix, react, and after the reaction is completed, filter it, wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 80° C. for 12 hours to obtain olefinated basalt fiber;
[0011] Step 4: adding polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, olefinic basalt fiber and initiator into a high-speed mixer, mixing evenly, and then putting into a twin-screw extruder for melt blending and extrusion granulation to obtain modified polypropylene;
[0012] Step 5: drying the polypropylene at a temperature of 80°C for 6 hours. After drying, uniformly mix the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant, melt blend in a twin-screw extruder, extrude and granulate to obtain a masterbatch, feed the masterbatch into a microrheometer, extrude and shape, and obtain a modified high-strength polypropylene composite fiber.
[0013] Preferably, in the step 1, the mass ratio of nano-calcium carbonate, N,N-dimethylformamide and 1,8-diisocyanate is 100:2500-3000:90-120.
[0014] Preferably, the reaction temperature in step 1 is 95-105° C., and the reaction time is 6-10 h.
[0015] Preferably, in the step 2, the mass ratio of isocyanate calcium carbonate, N,N-dimethylformamide, 1,3-bis(aminopropyl)tetramethyldisiloxane, and stannous octoate is 100:3200-3500:135-150:1-1.5.
[0016] Preferably, the reaction temperature in step 2 is 95-105° C., and the reaction time is 5-8 h.
[0017] Preferably, in the step 3, the mass ratio of the cleaned basalt fiber, the ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1200-1500:30-40.
[0018] Preferably, in step 3, the reaction temperature is 25-35° C., and the reaction time is 8-10 h.
[0019] Preferably, the ethanol solution in step three is a 50% ethanol aqueous solution.
[0020] Preferably, in the step 4, the mass ratio of polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, olefinic basalt fiber and initiator is 100:1.5-3:2-3:6-10:0.5-1.
[0021] Preferably, the temperature of melt blending in step 4 is 185-200° C. and the rotation speed is 100-200 r / min.
[0022] Preferably, the initiator in step 4 is di-tert-butyl peroxide isopropylbenzene.
[0023] Preferably, in the step 5, the mass ratio of the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant is 100:4-7:1-3:0.1-0.3, and the temperature of melt blending is 190-210°C.
[0024] Preferably, the antioxidant in step five is antioxidant 1010.
[0025] Preferably, in step 5, the extrusion molding is carried out through a circular spinning hole with a diameter of 2 mm in a microrheometer, the extrusion molding temperature is 210-230° C., and the extrusion speed is 10 m / min.
[0026] A modified high-strength polypropylene composite fiber prepared by adopting the preparation method of the modified high-strength polypropylene composite fiber.
[0027] (III) Beneficial technical effects
[0028] In the present invention, 1,8-diisocyanate is used to modify nano-calcium carbonate, and the isocyanate groups on the 1,8-diisocyanate react with the hydroxyl groups on the surface of the nano-calcium carbonate to obtain isocyanated calcium carbonate. The unreacted isocyanate groups on the isocyanated calcium carbonate react with the amino groups on 1,3-bis(aminopropyl)tetramethyldisiloxane under the action of a catalyst, stannous octoate, to obtain amino calcium carbonate. Acetone is used to activate basalt fiber, and then γ-methacryloxypropyltrimethoxysilane is used to modify the basalt fiber, and alkenyl groups are introduced into the basalt fiber to obtain alkenyl basalt fiber. Polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, and alkenyl basalt fiber are polymerized under the action of an initiator to obtain modified polypropylene, and the basalt fiber is introduced into the polypropylene, and anhydride groups are introduced at the same time. The dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant are mixed evenly, melt-blended, extruded into granules, and then extruded into a micro-rheometer to obtain a modified high-strength polypropylene composite fiber.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The nano calcium carbonate used in the present invention has the characteristics of easy availability of raw materials, low price, harmlessness to organisms, and a wide range of surface treatment agents. It is a filler with excellent mechanical properties. The modification of nano calcium carbonate effectively avoids the agglomeration of nano calcium carbonate. The introduced alkyl long chain and 1,3-bis (aminopropyl) tetramethyl disiloxane effectively improve the flexibility and mechanical properties of the matrix. Nano calcium carbonate can enhance the mechanical properties of the fiber, improve the strength and rigidity of the fiber, and form a nano-composite material. The amino group on the amino calcium carbonate can interact with the active group on the modified polypropylene, thereby enhancing the mechanical properties of the fiber. At the same time, the introduction of nano calcium carbonate can also serve as a heterogeneous nucleating agent to promote the crystallization of polypropylene, further improving its heat resistance, weather resistance and processing performance.
[0031] (2) The modified basalt fiber in the present invention has high strength and modulus, can improve the tensile strength and elongation at break of polypropylene fiber, and improve the strength of polypropylene fiber. After the basalt fiber is modified, in-situ polymerization occurs to obtain modified polypropylene, which has excellent compatibility with polypropylene, improves the dispersibility of the basalt fiber, can be evenly dispersed in the matrix, and greatly improves the toughness of the matrix. Polypropylene is modified by maleic anhydride, polar groups are introduced, and the interaction force between polypropylene and polar materials, such as hydrogen bonding or ionic bonding, improves the dispersibility and processing performance of the polypropylene composite fiber, improves the compatibility and adhesion between the polypropylene matrix and the basalt fiber and nano-calcium carbonate, and the dispersibility and processing performance are improved. Nano-calcium carbonate and basalt fiber work synergistically, and the obtained polypropylene composite fiber has excellent mechanical properties. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] A method for preparing a modified high-strength polypropylene composite fiber comprises the following steps:
[0035] Step 1, ultrasonically dispersing nano calcium carbonate into N,N-dimethylformamide, mixing evenly, adding 1,8-diisocyanate, wherein the mass ratio of the added nano calcium carbonate, N,N-dimethylformamide, and 1,8-diisocyanate is 100:2500:90, heating and stirring, reacting at 95°C for 10 hours, after the reaction is completed, filtering, washing with anhydrous ethanol, and drying in a drying oven at 80°C for 12 hours to obtain isocyanate calcium carbonate;
[0036] Step 2: ultrasonically disperse isocyanate calcium carbonate in N,N-dimethylformamide, mix well, add 1,3-bis(aminopropyl)tetramethyldisiloxane and stannous octoate in a mass ratio of 100:3200:135:1, heat and heat, stir and mix, react at 95°C for 8 hours, and after the reaction is completed, distill under reduced pressure, wash with anhydrous ethanol, and dry in a drying oven at 80°C for 12 hours to obtain amino calcium carbonate;
[0037] Step 3: Use acetone to ultrasonically clean the basalt fiber for 4 hours, transfer it to a 50% ethanol aqueous solution after cleaning, and then add γ-methacryloxypropyltrimethoxysilane, wherein the mass ratio of the cleaned basalt fiber, the ethanol solution, and the γ-methacryloxypropyltrimethoxysilane is 100:1200:30, stir and mix, react at 25°C, and react for 10 hours. After the reaction is completed, filter it, wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 80°C for 12 hours to obtain olefinated basalt fiber;
[0038] Step 4: adding polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, olefinated basalt fiber and initiator di-tert-butyl peroxide isopropylbenzene in a mass ratio of 100:1.5:2:6:0.5 to a high-speed mixer, mixing evenly, and then putting into a twin-screw extruder for melt blending. The melt blending temperature is 185° C., the rotation speed is 100 r / min, and extrusion granulation is performed to obtain modified polypropylene;
[0039] Step 5, the polypropylene is dried at a temperature of 80°C and a drying time of 6 hours. After drying, the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant 1010 are evenly mixed in a mass ratio of 100:4:1:0.1, melt blended in a twin-screw extruder at a melt blending temperature of 190°C, extruded and granulated to obtain a masterbatch, and the masterbatch is fed into a microrheometer, and extruded through a circular spinning hole with a diameter of 2 mm in the microrheometer. The extrusion molding temperature is 210°C and the extrusion speed is 10 m / min to obtain a modified high-strength polypropylene composite fiber.
[0040] Example 2
[0041] A method for preparing a modified high-strength polypropylene composite fiber comprises the following steps:
[0042] Step 1, ultrasonically dispersing nano calcium carbonate into N,N-dimethylformamide, mixing evenly, adding 1,8-diisocyanate, wherein the mass ratio of the added nano calcium carbonate, N,N-dimethylformamide, and 1,8-diisocyanate is 100:2800:105, heating and heating, stirring and mixing, reacting at 100°C for 8 hours, after the reaction is completed, filtering, washing with anhydrous ethanol, and drying in a drying oven at 80°C for 12 hours to obtain isocyanate calcium carbonate;
[0043] Step 2: ultrasonically disperse isocyanate calcium carbonate in N,N-dimethylformamide, mix well, add 1,3-bis(aminopropyl)tetramethyldisiloxane and stannous octoate in a mass ratio of 100:3400:145:1.2, heat and heat, stir and mix, react at 100°C for 6 hours, and after the reaction is completed, distill under reduced pressure, wash with anhydrous ethanol, and dry in a drying oven at 80°C for 12 hours to obtain amino calcium carbonate;
[0044] Step 3, using acetone to ultrasonically clean the basalt fiber for 4 hours, after cleaning, transfer it to a 50% ethanol aqueous solution, and then add γ-methacryloxypropyltrimethoxysilane, wherein the mass ratio of the cleaned basalt fiber, the ethanol solution, and the γ-methacryloxypropyltrimethoxysilane is 100:1400:35, stir and mix, react at 30°C, and the reaction time is 9 hours. After the reaction is completed, filter, wash with anhydrous ethanol, and dry in a vacuum drying oven at 80°C for 12 hours to obtain olefinated basalt fiber;
[0045] Step 4: adding polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, olefinic basalt fiber and initiator di-tert-butyl peroxide isopropylbenzene in a mass ratio of 100:2.1:2.5:8:0.8 to a high-speed mixer, mixing evenly, and then putting into a twin-screw extruder for melt blending at a temperature of 195° C. and a rotation speed of 150 r / min, extruding and granulating to obtain modified polypropylene;
[0046] Step 5, the polypropylene is dried at a temperature of 80°C and a drying time of 6 hours. After drying, the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant 1010 are evenly mixed in a mass ratio of 100:5:1.5:0.2, melt blended in a twin-screw extruder at a melt blending temperature of 205°C, extruded and granulated to obtain a masterbatch, and the masterbatch is fed into a microrheometer, and extruded through a circular spinning hole with a diameter of 2 mm in the microrheometer. The extrusion molding temperature is 225°C and the extrusion speed is 10 m / min to obtain a modified high-strength polypropylene composite fiber.
[0047] Example 3
[0048] A method for preparing a modified high-strength polypropylene composite fiber comprises the following steps:
[0049] Step 1, the polypropylene is dried at a temperature of 80 ° C and a drying time of 6 hours. After drying, the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant 1010 are mixed uniformly in a mass ratio of 100:6:2.1:0.2, melt blended in a twin-screw extruder at a melt blending temperature of 205 ° C, extruded and granulated to obtain a masterbatch, and the masterbatch is fed into a microrheometer, and extruded through a circular spinning hole with a diameter of 2 mm in the microrheometer. The extrusion molding temperature is 225 ° C, and the extrusion speed is 10 m / min to obtain a modified high-strength polypropylene composite fiber.
[0050] The preparation methods of the modified polypropylene and the amino calcium carbonate are the same as those of the modified polypropylene and the amino calcium carbonate in Example 2.
[0051] Example 4
[0052] A method for preparing a modified high-strength polypropylene composite fiber comprises the following steps:
[0053] Step 1, ultrasonically dispersing nano calcium carbonate into N,N-dimethylformamide, mixing evenly, adding 1,8-diisocyanate, wherein the mass ratio of the added nano calcium carbonate, N,N-dimethylformamide, and 1,8-diisocyanate is 100:3000:120, heating and stirring, reacting at 105°C for 6 hours, after the reaction is completed, filtering, washing with anhydrous ethanol, and drying in a drying oven at 80°C for 12 hours to obtain isocyanate calcium carbonate;
[0054] Step 2: ultrasonically disperse isocyanate calcium carbonate in N,N-dimethylformamide, mix well, add 1,3-bis(aminopropyl)tetramethyldisiloxane and stannous octoate in a mass ratio of 100:3500:150:1.5, heat and heat, stir and mix, react at 105°C for 5 hours, and after the reaction is completed, distill under reduced pressure, wash with anhydrous ethanol, and dry in a drying oven at 80°C for 12 hours to obtain amino calcium carbonate;
[0055] Step 3, using acetone to ultrasonically clean the basalt fiber for 4 hours, after cleaning, transfer it to a 50% ethanol aqueous solution, and then add γ-methacryloxypropyltrimethoxysilane, wherein the mass ratio of the cleaned basalt fiber, the ethanol solution, and the γ-methacryloxypropyltrimethoxysilane is 100:1500:40, stir and mix, react at 35°C, and the reaction time is 8 hours. After the reaction is completed, filter, wash with anhydrous ethanol, and dry in a vacuum drying oven at 80°C for 12 hours to obtain olefinated basalt fiber;
[0056] Step 4: Add polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, olefinated basalt fiber and initiator di-tert-butyl peroxide isopropylbenzene in a mass ratio of 100:3:3:10:1 into a high-speed mixer, mix well, put into a twin-screw extruder for melt blending, the melt blending temperature is 200° C., the rotation speed is 200 r / min, and extrusion granulation is performed to obtain modified polypropylene;
[0057] Step 5, the polypropylene is dried at a temperature of 80°C and a drying time of 6 hours. After drying, the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant 1010 are evenly mixed in a mass ratio of 100:7:3:0.3, melt blended in a twin-screw extruder at a melt blending temperature of 210°C, extruded and granulated to obtain a masterbatch, and the masterbatch is fed into a microrheometer, and extruded through a circular spinning hole with a diameter of 2 mm in the microrheometer. The extrusion molding temperature is 230°C and the extrusion speed is 10 m / min to obtain a modified high-strength polypropylene composite fiber.
[0058] Comparative Example 1
[0059] A method for preparing polypropylene composite fiber comprises the following steps:
[0060] Step 1, drying the polypropylene at a temperature of 80 ° C and a drying time of 6 hours. After drying, the dried polypropylene, maleic anhydride grafted polypropylene, basalt fiber, amino calcium carbonate and antioxidant 1010 with a mass ratio of 100:5.5:0.5:2.1:0.2 are mixed evenly, melt blended in a twin-screw extruder at a melt blending temperature of 205 ° C, extruded and granulated to obtain a masterbatch, and the masterbatch is fed into a microrheometer, and extruded through a circular spinning hole with a diameter of 2 mm in the microrheometer. The extrusion molding temperature is 225 ° C, and the extrusion speed is 10 m / min to obtain a polypropylene composite fiber.
[0061] The preparation method of the aminated calcium carbonate is the same as that of the aminated calcium carbonate in Example 2.
[0062] Comparative Example 2
[0063] A method for preparing polypropylene composite fiber comprises the following steps:
[0064] Step 1, drying the polypropylene at a temperature of 80°C for a drying time of 6 hours. After drying, the dried polypropylene, modified polypropylene, nano-calcium carbonate and antioxidant 1010 are uniformly mixed in a mass ratio of 100:6:2.1:0.2, melt blended in a twin-screw extruder at a melt blending temperature of 205°C, extruded and granulated to obtain a masterbatch, and the masterbatch is fed into a microrheometer, and extruded through a circular spinning hole with a diameter of 2 mm in the microrheometer, the extrusion molding temperature is 225°C, and the extrusion speed is 10m / min to obtain a polypropylene composite fiber.
[0065] The preparation method of the modified polypropylene is the same as that of the modified polypropylene in Example 2.
[0066] Comparative Example 3
[0067] A method for preparing polypropylene composite fiber comprises the following steps:
[0068] Step 1, drying the polypropylene at a temperature of 80°C for a drying time of 6 hours. After drying, the dried polypropylene, maleic anhydride grafted polypropylene, basalt fiber, nano-calcium carbonate and antioxidant 1010 in a mass ratio of 100:5.5:0.5:2.1:0.2 are mixed evenly, melt blended in a twin-screw extruder at a melt blending temperature of 205°C, extruded and granulated to obtain a masterbatch, and the masterbatch is fed into a microrheometer, and extruded through a circular spinning hole with a diameter of 2 mm in the microrheometer, the extrusion molding temperature is 225°C, and the extrusion speed is 10 m / min to obtain a polypropylene composite fiber.
[0069] The nano-calcium carbonate used in the embodiments and comparative examples of the present invention was purchased from Shanxi Ruicheng Warner Nanomaterials Co., Ltd., with an average particle size of 60-80 nm; polypropylene was purchased from PetroChina Sichuan Petrochemical Co., Ltd., model L5E89; basalt fiber was purchased from Sichuan Qianyi Composite Materials Co., Ltd., with a length of 3 mm and a diameter of 10 μm; all raw materials used without other explanations were commercially available raw materials.
[0070] Corresponding tests were performed on the polypropylene composite fibers prepared in Examples 1-4 and Comparative Examples 1-3. The test methods and test results are as follows:
[0071] Strength test: The mechanical properties of the composite fiber were tested using a YG021A-Ⅲ electronic single yarn strength tester. Each group was tested 5 times on average and the average value was taken. The test results are shown in Table 1:
[0072] Table 1
[0073]
[0074] According to the test results in Table 1, it can be seen that the corresponding polypropylene composite fibers in Examples 1-4 have excellent mechanical properties and high strength. In Comparative Example 1, the basalt fiber was not modified and directly mixed with polypropylene, resulting in poor dispersibility and compatibility, and poor mechanical properties. In Comparative Example 2, the nano-calcium carbonate was not modified, and the nano-calcium carbonate was prone to agglomeration, resulting in decreased comprehensive properties. In Comparative Example 3, nano-calcium carbonate and basalt fiber were directly added, resulting in greatly reduced comprehensive properties and low mechanical strength.
[0075] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A method for preparing a modified high-strength polypropylene composite fiber, characterized in that: The steps include: Step 1: Ultrasonically disperse nano calcium carbonate in N,N-dimethylformamide, mix well, add 1,8-diisocyanate, heat and stir to react, filter after the reaction is completed, wash, and dry in a drying oven at 80°C for 12 hours to obtain isocyanate calcium carbonate; Step 2: ultrasonically disperse isocyanate calcium carbonate in N,N-dimethylformamide, mix well, add 1,3-bis(aminopropyl)tetramethyldisiloxane and stannous octoate, heat and stir to react, and after the reaction is completed, perform vacuum distillation, wash, and dry in a drying oven at 80° C. for 12 hours to obtain amino calcium carbonate; Step 3: Use acetone to ultrasonically clean the basalt fiber for 4 hours, transfer it to an ethanol solution after cleaning, add γ-methacryloxypropyltrimethoxysilane, stir and mix, react, and after the reaction is completed, filter, wash, and dry in a vacuum drying oven at 80° C. for 12 hours to obtain olefinated basalt fiber; Step 4: adding polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, olefinic basalt fiber and initiator into a high-speed mixer, mixing evenly, and then putting into a twin-screw extruder for melt blending and extrusion granulation to obtain modified polypropylene; Step 5: drying the polypropylene at a temperature of 80°C for 6 hours. After drying, uniformly mixing the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant, melt blending in a twin-screw extruder, extruding and granulating to obtain a masterbatch, feeding the masterbatch into a microrheometer, extruding and molding, and obtaining a modified high-strength polypropylene composite fiber.
2. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: In the step 1, the mass ratio of nano-calcium carbonate, N,N-dimethylformamide and 1,8-diisocyanate is 100:2500-3000:90-120, the reaction temperature is 95-105° C., and the reaction time is 6-10 hours.
3. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: In the step 2, the mass ratio of isocyanate calcium carbonate, N,N-dimethylformamide, 1,3-bis(aminopropyl)tetramethyldisiloxane, and stannous octoate is 100:3200-3500:135-150:1-1.
5.
4. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: The reaction temperature in step 2 is 95-105° C., and the reaction time is 5-8 hours.
5. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: In the step 3, the mass ratio of the cleaned basalt fiber, the ethanol solution, and γ-methacryloxypropyltrimethoxysilane is 100:1200-1500:30-40, the reaction temperature is 25-35° C., and the reaction time is 8-10 hours.
6. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: In the step 4, the mass ratio of polypropylene, maleic anhydride, styrene-isoprene-styrene block copolymer, olefinic basalt fiber and initiator is 100:1.5-3:2-3:6-10:0.5-1.
7. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: The temperature of the melt blending in the step 4 is 185-200° C. and the rotation speed is 100-200 r / min.
8. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: In the step 5, the mass ratio of the dried polypropylene, modified polypropylene, amino calcium carbonate and antioxidant is 100:4-7:1-3:0.1-0.3, and the temperature of melt blending is 190-210°C.
9. The method for preparing a modified high-strength polypropylene composite fiber according to claim 1, characterized in that: In the step 5, the microrheometer is used for extrusion molding through a circular spinning hole with a diameter of 2 mm, the extrusion molding temperature is 210-230° C., and the extrusion speed is 10 m / min.
10. A modified high-strength polypropylene composite fiber prepared by the method for preparing a modified high-strength polypropylene composite fiber according to any one of claims 1 to 9.
Citation Information
Patent Citations
Crude polypropylene fiber and preparation method thereof
CN102383214A
Preparation method of polypropylene / carbon nanotube fiber composite material
CN110818998A
Basalt fiber enhanced polypropylene composite plastic for automobile interior parts
CN103450562A
Continuous basalt fiber surface treating agent and preparation method thereof
CN112126123A
Environment-friendly high-performance PVC water supply pipe and preparation method thereof
CN118085476A
Cited By
High-strength flame-retardant sealing strip and preparation method thereof
CN120098377A